Hikmat Ilahiya: Suhrawardian Divine Metaphysics - Uždavinys, Algis (Acta Orientalia Vilnensia, 2000)
The article deals with Yahya ibn Habash Amirak al–Suhrawardi’s (1155–1191) ‘oriental theosophy’ (hikmat alishraq) and its hidden Neoplatonic (especially Plotinian) as well as Hermetic and Zoroastrian background. Suhrawardi regarded a light not simply as a symbol of divine manifestation, but as the fundamental reality of all things. At the same time the Platonic theory of Ideas was transformed into a sort of Zoroastrian angelology, and Sufism mixed with philosophy and Neoaristotelian cosmology in order to create the Islamic theosophy of Ishraq. Hakim muta’allih, the sage of Suhrawardian theosophy resembles the Neoplatonic hieratic sage who practices theurgy and whose aim consists in a direct experience of the divine (illumination and theosis). The eclectic marriage of pre–Islamic Iranian religious terminology and Hellenic philosophy within the general framework of the Ishraqi tradition is one of the most distinctive features of al–Suhrawardi’s theology.